Semiotics Analysis on Maanagaram (2017) (Journal of Advanced Research in Journalism & Mass Communication, 2022)
The study based on the semiotic analysis of the movie Maanagaram (2017) by understanding the role of mise-en-scene in effective narration. This is done in both the visual arts through storyboarding, visual theme, cinematography, as well as in narrative storytelling through direction. All though the script is complicated the screenplay was very engaging and a the characters in the movie were we developed and relatable to the audience. All though the script is complicated the screenplay was very engaging and all the characters in the movie were we developed and relatable to the audience. Semiotic analysis is an important approach for fully comprehending the nuance of a film. This method seeks to establish the relationship between the Signifier and the Signified, as well as how they produce a meaningful interpretation. How to cite this article: Seshadri E. Semiotics analysis on Maanagaram (2017). J Adv Res Jrnl Mass Comm 2022; 9(3&4): 21-25. DOI: https://doi.org/10.24321/2395.3810.202205